OPTIMALISASI PERAN DANA BAGI HASIL (DBH) DALAM PEMBANGUNAN DAERAH - Isti'anah Isti'anah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2008)
The implementation of fiscal balance policy has been done through budgetallocation for the local governments, include balance fund. The fiscal balance policy would reduce imbalance fund resources between central and local governments and to lessen fiscal gap among local governments as well. One of the fiscal balance components is revenue sharing. Problems often arising in delivering revenue sharing mechanism are the implementation of quarter periodical that are not on time. As consequence, it would disturb planning system of development in regions.